PENGEMBANGAN LATIHAN SOAL KETERAMPILAN MEMBACA PEMAHAMAN BAHASA JERMAN PADA MEDIA QUIZALIZE UNTUK SISWA KELAS XI - Pagar, Oktaviani; Pujosusanto, Ari (LATERNE, 2025)
The This study aimed to develop reading comprehension exercises in German for Grade XI students using the interactive platform Quizalize. The research was motivated by students’ low reading comprehension skills, limited learning media, and the lack of technology-based practice materials. Using the Borg and Gall R&D model (limited to five stages), the research included product design, expert validation, and revision. Validation instruments were used to assess both content and media. Results showed the exercises were highly suitable, with content validation scoring 82.86% and media 92%. Of the 20 questions developed, 85% were categorized as easy and 15% as difficult, indicating that the exercises were appropriate for students’ proficiency levels and effective for classroom use.